Anthropometric Assessment of Nepali Children Institutionalized in Orphanages - Lucía Fernández; Ana Rubini; Jose M. Soriano; Joaquín Aldás-Manzano; Jesús Blesa (MDPI AG, 2020)
Nepal is among the world's poorest countries, and it is the third-poorest country in the South Asian region. Asia has the largest number of orphans in the world; in Nepal there are around 13,281 orphan children. The objective of this study is to evaluate the growth status of institutionalized children in Nepal through the analyses of anthropometric measures. The sample was Nepalese children aged 4 to 17, obtained from two different orphanages: in the first one, children with physical and mental disabilities coexist with children without any conditions. In the second one, there were no subjects with disabilities. Significant evidence of an association between mental and physical disability in institutionalized children and undernutrition (wasting and stunting) was found in this study. There is also weak but significant evidence of a relationship between underweight and being male. The study could help reaching a better understanding of growth status of institutionalized children in Nepal.